Laparoscopic Nephrectomy with Adrenalectomy for Synchronous Adrenal Myelolipoma and Renal Cell Carcinoma - Kallappan Senthil; Manickam Ramalingam; Karpagam Janardhan; Anandan Murugesan; Mizar Ganapathy Pai (Case Reports in Urology, 2015)
Introduction. Adrenal myelolipomas are uncommon nonfunctioning tumors of the adrenal. Synchronous renal cell carcinomas with adrenal myelolipomas are very rare. We present the case report of adrenal myelolipoma with synchronous RCC managed laparoscopically. Case Report. A 60-year-old old gentleman presented with incidental right upper polar mass with right adrenal mass. Metastatic work-up was negative. Laparoscopic radical nephrectomy with adrenalectomy was done under general anesthesia. The biopsy report was right kidney clear cell adenocarcinoma (T1b) with right adrenal myelolipoma. Conclusion. This is the first case report of laparoscopic adrenalectomy with nephrectomy for ipsilateral synchronous renal cell carcinoma with adrenal myelolipoma.